APPLICATION OF BINDU AND MANDALA AS A MODEL FOR CULTURAL AND SACRED ARCHITECTURE - Ayub Khan, Jaffer Adam; Varadarajan, Deepika (Journal of Architecture, Planning and Construction Management, 2016)
This paper examines the concept of Vastu Purusha through â€œbinduâ€ and â€œmandalaâ€ which have been the primary form generators in the architecture of several Asian cultures and particularly in India. Through literary resources this paper examines the ability of Sri Yantra to unpack itself into various progressive spatial geometries that have inherent relationships which attain its final form as the â€œmandalaâ€, which is also known as the â€œmask of God through which eternity is to be achieved.â€ The â€œmandalaâ€ is the Hindu cosmic model through which the Buddhist cosmic thinking is evolved. The first part of this paper discusses about the mandala model and its systematic structure which inspires in constructing spatial systems that build architectural spaces. The pioneering practice for three decades in architecture forms the basis of practice based research methodology. This will examine the real time architectural projects that demonstrate how the various elements of nature that manifests within the mandala and the geometries help generate an ephemeral form as a symbol of spirituality and awakening of consciousness. The objective of this paper is to present the work on a â€œPeace Museumâ€ project in Sri Lanka which bridges the spiritual philosophy of Hindu-Buddhist culture, where the mandala evolves a paradigm for a contemporary architectural thought associated with the sacredness of built spaces.